Choice of Intensive Lifestyle Change and/or Metformin after Shared Decision Making for Diabetes Prevention: Results from the Prediabetes Informed Decisions and Education (PRIDE) Study. (July 2021) - Moin, Tannaz; Martin, Jacqueline M.; Mangione, Carol M.; Grotts, Jonathan; Turk, Norman; Norris, Keith C.; Tseng, Chi-Hong; Jeffers, Kia Skrine; Castellon-Lopez, Yelba; Frosch, Dominick L.; Duru, O. Kenrik
Introduction: While the Diabetes Prevention Program Study demonstrated that intensive lifestyle change and metformin both reduce type 2 diabetes incidence, there are little data on patient preferences in real-world, clinical settings. Methods: The Prediabetes Informed Decisions and Education (PRIDE) study was a cluster-randomized trial of shared decision making (SDM) for diabetes prevention. In PRIDE, pharmacists engaged patients with prediabetes in SDM using a decision aid with information about both evidence-based options. We recorded which diabetes prevention option(s) participants chose after the SDM visit. We also evaluated logistic regression models examining predictors of choosing intensive lifestyle change ± metformin, compared to metformin or usual care, and predictors of choosing metformin ± intensive lifestyle change, compared to intensive lifestyle change or usual care. Results: Among PRIDE participants ( n = 515), 55% chose intensive lifestyle change, 8.5% chose metformin, 15% chose both options, and 21.6% declined both options. Women (odds ratio [OR] = 1.60, P = 0.023) had higher odds than men of choosing intensive lifestyle change. Patients >60 years old (OR = 0.50, P = 0.028) had lower odds than patients <50 years old of choosing metformin. Participants with higher body mass index (BMI) had higher odds of choosing intensive lifestyle change (OR = 1.07 per BMI unit increase, P = 0.005) v. other options and choosing metformin (OR = 1.06 per BMI unit increase, P = 0.008) v. other options. Conclusions: Patients with prediabetes are making choices for diabetes prevention that generally align with recommendations and expected benefits from the published literature. Our results are important for policy makers and clinicians, as well as program planners developing systemwide approaches for diabetes prevention.